Answer:
There's one solution
(0,5)
Explanation:
There's one solution
We can tell this is true because of the 3x in the second on and just hte x in the first. If you look closely you'll see the coefficents for the x values is the only difference between the two.
Let's now solve
We need to get a positive variable by itself
let's take x+y=5 and solve for y
x-5= -y
y= -x+5
We can then plug this y value into the other equation
3x-(-x+5)= -5
3x+x-5= -5
4x= 0
x=0
Let's then plug this value in for x into any of the beginning equations
0+y=5
y=5